Urban Planning Stakeholders on Nocturnal Lighting in the City of Montreal - Sylvain Bertin; Sylvain Paquette (Bollettino della Società Geografica Italiana, 2019)
Lighting has become an important tool for cities as they compete to market their territories. The evolution of lighting strategies responds to a progressive change in the way professionals engage with the design aspect of nocturnal urban spaces. But, what are the main objectives behind these new approaches and interventions? How do stakeholders consider night-time and how do their representations structure the urban landscape? In order to better understand the organization of the city at night, this paper will explore the representations of landscapes from a sociocultural perspective. Using the example of Montreal, Canada, a city that is particularly representative of trends in scripting the urban experience, this research discloses a process of adding value to central spaces while neglecting ordinary landscapes. In this regard, this study reveals the tensions between illuminated and dark spaces, contributing to a better understanding of the relationship that Western society has with darkness while also unveiling the spatial hierarchy between the different areas of the city.